Quantitative analysis of 3D cellular geometry and modelling of the Arabidopsis embryo. (12th July 2022) - Yoshida, Saiko; Weijers, Dolf
Abstract: As many multicellular organisms, land plants start their life as a single cell, which forms an embryo. Embryo morphology is relatively simple, yet comprises basic tissues and organs, as well as stem cells that sustain post‐embryonic development. Being condensed in both time and space, early plant embryogenesis offers an excellent window to study general principles of plant development. However, it has been technically challenging to obtain high spatial microscopic resolution, or to perform live imaging, that would enable an in‐depth investigation. Recent advances in sample preparation and microscopy now allow studying the detailed cellular morphology of plant embryos in 3D. When coupled to quantitative image analysis and computational modelling, this allows resolving the temporal and spatial interactions between cellular patterning and genetic networks. In this review, we discuss examples of interdisciplinary studies that showcase the potential of the early plant embryo for revealing principles underlying plant development. General Summary: Multicellular land plants begin their life as single cells. In many species, such single cells form embryos, miniature versions of the adult plant. While an embryo already has basic structures consisting of an adult plant, its structure is far simpler than an adult plant. Therefore, embryos can be a good model for studying how plant cell types, organs and bodies are formed. During embryo development, cells grow and divide, and these cells are specified towards different fates. We review how advances in microscopic imaging, image analysis and computational modelling have helped us understand mechanisms underlying the growth and development of plant embryos. Importantly, the use of 3D data allows to quantitatively analyze the shape of cells in embryos and the information obtained from such quantitative analysis can be used to develop computational modelling which enables to resolve the complex interactions between genes and cell morphology.